Effect of Modified Blumgart Anastomosis on Surgical Outcomes After Pancreaticoduodenectomy - Özşay, Oğuzhan; Aydın, Mehmet Can (Turkish Journal of Gastroenterology, 2022)
Background: Surgeons continue to be concerned about complications after pancreaticoduodenectomy, especially postoperative pancreatic fistula. Among the factors that cause postoperative pancreatic fistula, the pancreaticojejunostomy technique has stood out in recent studies. In this study, we aimed to compare the surgical outcomes, especially POPF, of the modified Blumgart and the traditional anastomosis techniques in patients who underwent pancreaticoduodenectomy. Methods: A total of 144 patients who underwent pancreaticoduodenectomy were divided into 2 groups according to the performed pancreaticojejunostomy technique (modified Blumgart anastomosis, n = 91 and traditional anastomosis, n = 53). Preoperative clinicodemographic data, perioperative findings, and postoperative results were compared between the groups. Additionally, factors associated with clinically relevant postoperative pancreatic fistula were analyzed. Results: The modified Blumgart anastomosis group had lower clinically relevant postoperative pancreatic fistula rate than traditional anastomosis group (n = 8 (8.8%) versus n = 14 (26.4%), P = .005). On the contrary, the biochemical leakage rate was higher in the modified Blumgart anastomosis group (n = 30 (33%) versus n = 9 (17%), P = .037). While postoperative pancreatic fistula-related reoperation rate was lower (n = 2 (2.2%) versus n = 7 (13.2%), P = .013), the length of hospital stay was also shorter (11 days (5-47 days) versus 21 days (6-46 days), P < .001) in the modified Blumgart anastomosis group. Univariate and multivariate analyses revealed that modified Blumgart anastomosis was an independent and negative predictive factor for clinically relevant postoperative pancreatic fistula (odds ratio = 0.274, 95% confidence interval = 0.103-0.728, P = .009). Conclusion: Compared to the traditional anastomosis, modified Blumgart anastomosis decreases the rate of transition from biochemical leakage to clinically relevant postoperative pancreatic fistula and postoperative pancreatic fistula-related reoperation and also shortens the length of hospital stay. In addition, modified Blumgart anastomosis is an independent and negative predictive factor for the development of clinically relevant postoperative pancreatic fistula.